Stock Market Development and Economic Growth: The Case of Kazakhstan - Akanayeva, Tolkyn (Journal of Finance and Financial Law, 2024)
The purpose of the article. The relationship between economic growth and financial development has long been widely discussed in scientific circles. Most empirical research has led to the clear conclusion that financial markets stimulate economic development. However, in the case of financial markets in developing countries, this conclusion is not so obvious. The aim of this study is to empirically verify the relationship between economic growth and the development of the stock market (Kazakhstan Stock Exchange).Methodology. Empirical verification of the strength and shape of the cause-and-effect relationship between real GDP growth and independent predictors will be carried out using classic linear regression models with many independent variables.Results of the research. The results of empirical verification of the strength and shape of the cause-and-effect relationship between the growth of real GDP and independent predictors indicate that the development of the stock market has a positive impact on the growth of the country's real GDP but is not the basic factor of Kazakhstan's economic growth.